Distribution, Evolution, Catalytic Mechanism, and Physiological Functions of the Flavin-Based Electron-Bifurcating NADH-Dependent Reduced Ferredoxin: NADP+ Oxidoreductase - Liang, Jiyu; Huang, Haiyan; Wang, Shuning (Frontiers in Microbiology, 2019)
NADH-dependent reduced ferredoxin:NADP+ oxidoreductase (Nfn) is an electron-bifurcating enzyme first discovered in the strict anaerobes Clostridium kluyveri and Moorella thermoacetica. In vivo, Nfn catalyzes the endergonic reduction of NADP+ with NADH coupled to the exergonic reduction of NADP+ with reduced ferredoxin. Most Nfn homologs consist of two subunits, although in certain species Nfn homologs are fused. In contrast to other electron-bifurcating enzymes, Nfn possess a simpler structure. Therefore, Nfn becomes a perfect model to determine the mechanism of flavin-based electron bifurcation, which is a novel energy coupling mode distributed among anaerobic bacteria and archaea. The crystal structures of Nfn from Thermotoga maritima and Pyrococcus furiosus are known, and studies have shown that the FAD molecule of the NfnB (b-FAD) is the site of electron bifurcation, and other cofactors, including a [2Fe2S] cluster, two [4Fe4S] clusters, and the FAD molecule on the NfnA subunit, contribute to electron transfer. Further, the short-lived anionic flavin semiquinone (ASQ) state of b-FAD is essential for electron bifurcation. Nfn homologs are widely distributed among microbes, including bacteria, archaea, and probably eukaryotes, most of which are anaerobes despite that certain species are facultative microbes and even aerobes. Moreover, potential evidence shows that lateral gene transfer may occur in the evolution of this enzyme. Nfn homologs present four different structural patterns, including the well-characterized NfnAB and three different kinds of fused Nfn homologs whose detailed properties have not been characterized. These findings indicate that gene fusion/fission and gene rearrangement may contribute to the evolution of this enzyme. Under physiological conditions, Nfn catalyzes the reduction of NADP+ with NADH and reduced ferredoxin, which is then used in certain NADPH-dependent reactions. Deletion of nfn in several microbes causes low growth and redox unbalance and may influence the distribution of fermentation products. It’s also noteworthy that different Nfn homologs perform different functions according to its circumstance. Physiological functions of Nfn indicate that it can be a potential tool in the metabolic engineering of industrial microorganisms, which can regulate the redox potential in vivo.